Individual and community-level factors associated with unmet need for contraception among reproductive-age women in Ethiopia; a multi-level analysis of 2016 Ethiopia Demographic and Health Survey - Melaku Yalew; Bezawit Adane; Bereket Kefale; Yitayish Damtie (BMC, 2020)
Abstract Background There is limited evidence on the unmet need for contraceptives among married reproductive-age women especially in developing countries like Ethiopia. Thus, this study aimed to assess individual and community-level factors associated with unmet need for contraception among reproductive-age women in Ethiopia. Method A secondary analysis was done on the 2016 Ethiopian Demographic and Health Survey (EDHS) dataset which were collected cross-sectional. A total of 9056 women who were fecund, married and/or sexually active were included in the analysis. Multi-level mixed-effect logistic regression analysis was done by STATA version 14.0 to identify individual and community-level factors. Adjusted odds ratio with 95% confidence interval was used to show the strength and direction of the association and statistical significance was declared at P value less than 0.05. Result Factors significantly associated with unmet need were; ages of women between 45 and 49 years [AOR = 2.25, 95% CI: (1.34, 3.79)], greater than or equal to three living children [AOR = 1.87, 95% CI: (1.40, 2.49)], belong to richer household [AOR = 0.73, 95% CI: (0.54, 0.97)], Muslim followers [AOR = 1.37, 95% CI: (1.02, 1.83)], married more than once [AOR = 1.31, 95% CI: (1.06, 1.62)]. From community level variables: belong to the Somali region [AOR = 0.34, 95% CI: (0.19, 0.61)] were significantly associated with unmet need. Conclusion Both individual and community-level factors were significant determinants of unmet need. From individual-level factors: advanced ages of women, many total numbers of living children, live in the richer wealth quintile, being Muslim follower and married more than once and from community-level variables: belong to the Somali region were significantly associated with unmet need for contraception. The findings suggested that health care providers should mainly focus on women nearly on menopauses, who live in the poorest household and who had many numbers of living children and married more than once to decrease the unmet need for contraceptives.